Associations of perceived social support, resilience and posttraumatic growth among young and middle-aged patients with first-episode psychosis - Zhao, Chongzheng; Zhao, Xiumei; Teng, Weiyu; Zou, Guiyuan (Frontiers in Psychiatry, 2025)
BackgroundThe prevalence of mental disorders among young and middle-aged populations has demonstrated a significant upward trend, with first-episode psychosis (FEP) frequently associated with psychological distress and functional impairments during initial onset. While persons affected by FEP frequently report psychological distress and reduced quality of life during early illness stages, they may also experience post-traumatic growth (PTG), which fosters positive changes that facilitate their recovery. Yet there is limited attention on PTG in young and middle-aged patients with FEP. Therefore, this study aimed to investigate the level of PTG and identify significant correlates and mediators of PTG among young and middle-aged patients with FEP.MethodsFrom January 2021 to December 2023, two hundred eight patients with first-episode psychosis were enrolled from a tertiary hospital in Shandong Province, China, through convenience sampling. The Perceived Social Support Scale (PSSS), Posttraumatic Growth Inventory-Short Form (PTGI-SF), and Connor-Davidson Resilience Scale (CD-RISC10) were administered. Hierarchical linear regression modeling was performed to examine the associations between perceived social support and PTG and the mediating effect of resilience.ResultsThe PTG score was 31.22 ± 6.59, and resilience and PSS could positively predict the variance in PTG. Resilience partially mediated the relationship between PSS and PTG, and the value of the mediating effect was 22.8%.ConclusionsYoung and middle-aged patients with FEP have a moderate level of PTG. Resilience partially mediates the relationship between PSS and PTG. Therefore, interventions focusing on promoting PSS and resilience should be developed to encourage PTG in young and middle-aged patients with FEP.